Standing balance post total knee arthroplasty: sensitivity to change analysis from four to twelve weeks in 466 patients. Issue 1 (January 2017) - Clark, R.A.; Seah, F.J.-T.; Chong, H.-C.; Poon, C.L.-L.; Tan, J.W.-M.; Mentiplay, B.F.; Pua, Y.-H.
Summary: Objective: Little is known about how static standing balance changes post total knee arthroplasty (TKA). The primary aim of this study was to examine the sensitivity to change and redundancy of center of pressure (COP) variables post-TKA. The secondary aim was to compare the sensitivity of these measures to standard clinical assessments of one repetition maximum knee extension strength and fast pace gait speed. Design: 466 participants performed instrumented double-limb standing balance tests with eyes open at 4 and 12 weeks post-TKA. Measures of COP standard deviation, amplitude, root mean square (RMS), path length, detrended fluctuation analysis (DFA) and signal frequency content for the medial-lateral (ML) and anterior-posterior (AP) axes were examined. Results: Significant decreases in total path length, ML variables related to sway velocity and AP signal complexity and frequency were observed. Inter-session Cohen's d effect size (ES) revealed the strongest effect was for high velocity ML path length, with a 12% decrease in this rapid sway. This variable, along with AP mean instantaneous frequency and AP DFA, were the only ones significantly different with effect sizes >0.20 and non-redundant (Spearman's rho <0.75). The ES of COP-derived variables (maximum = 0.45) were lower than gait speed (1.40) and knee extensor strength (1.54). Conclusion: Increased high velocity ML sway is present at four compared to 12 weeks post-TKA. This augmented rapid sway may provide increased challenges to the postural control system at a time coinciding with reduced strength levels, which could have implications for physical function during activities of daily living.